MINTERM AND IMPLICANT SELECTION CRITERIA FOR DIRECT COVER ALGORITHMS AND OFF-BASED MINTERM ORDERING - AKAR, Hakan; BAÅžÃ‡Ä°FTÃ‡Ä°, Fatih (Malaysian Journal of Computer Science, 2020)
This paper presents a new method for minimization of logic functions. We summarized minterm and implicant selection rules for direct cover algorithms and introduced OFF based ordering method. As other minterm and implicant selection algorithms use ON minterms and runs in minimization phase, they may not find real isolated minterms for insignificant functions. The proposed method uses OFF minterms for ordering minterms. Thus insignificant functions including Don’t Care minterms, could be handled easily with this approach. Results revealed that although proposed algorithm use running time in reordering process, it saves much time in simplification process. In addition, output functions are more simplified with OFF based ordering method.